Correlation between functional ability, toe flexor strength, and plantar pressure of hallux valgus in young female adults: a cross-sectional study - Mieko Yokozuka; Kanako Okazaki; Yuko Sakamoto; Koko Takahashi (Journal of Foot and Ankle Research, 2020)
Abstract Background The prevalence of hallux valgus (HV) increases with age in females. Several studies have investigated the relationship between foot problems, including HV, and falls in older individuals. This study aimed to examine whether HV causes a decline in functional activity in young females and also evaluate the relationship between HV angle, functional activity, toe flexor strength, and plantar pressure. Methods We assessed 94 females (mean age, 19.6 ± 1.3 years; mean body mass index, 21.2 ± 2.0 kg/m2) not currently receiving treatment for lower limb disease. HV angle was determined using their footprint. Functional reach (FR) and maximum step length (MSL), toe flexor strength, and plantar pressure were measured. Plantar pressure was measured during walking. We also calculated FR and the pressure in eight regions (first toe, second through fifth toes, first metatarsal, second through fourth metatarsals, fifth metatarsal, midfoot, medial heel, and lateral heel). Results There were 39 and 55 participants in the HV and no HV groups, respectively. FR and MSL did not differ significantly between the HV and no HV groups. Toe flexor strength was significantly different between the HV and no HV groups (26.69 ± 9.68 vs. 32.19 ± 8.55, respectively) (p = 0.002, β = 0.206). During walking, plantar pressure was significantly lower in the second through fifth toes in the HV group (p = 0.005, β = 0.187). During FR, plantar pressure was significantly greater in the first metatarsal in the HV group (p = 0.016, β = 0.338). HV angle was negatively correlated with toe flexor strength (r = − 0.315, p = 0.002, β = 0.121) and plantar pressure during walking in the second through fifth toes (r = − 0.362, p < 0.001, β = 0.047), and positively correlated with plantar pressure during FR in the first metatarsal (r = 0.308, p = 0.002, β = 0.137). Toe flexor strength was negatively correlated with plantar pressure during FR in the second through fourth metatarsals (r = − 0.318, p = 0.002, β = 0.115), and there was a positive correlation with MSL (r = 0.330, p = 0.001, β = 0.092). Conclusions This study confirmed that HV reduces toe flexor strength and affects forefoot pressure during walking and FR in young females. Moreover, the toe flexor strength affects MSL. Efforts to prevent the onset and deterioration of HV from a young age might help reduce the risk of falling when older.